Response of under-ground bud bank to degradation in an alpine meadows on the Qinghai-Tibet Plateau, China - Yang, Jun; Zhang, Min; Wang, Xiang-tao (Frontiers in Plant Science, 2022)
Exploring the diversity and formation mechanism of under-ground bud banks is essential for understanding the renewal of plant populations and community succession. However, there are few studies on the response of bud bank size and composition to different degradation gradients in alpine meadows. In view of this, we investigated the size and composition of bud bank under four degradation gradients (non-degraded:ND, lightly degraded:LD, moderately degraded:MD, and heavily degraded:HD) caused by overgrazing in a typical alpine meadow in Tibet, China, using a unit area excavation sampling method, and analyzed the correlation between above-ground plant community composition and bud bank density. Our results showed that: (i) in the ND alpine meadow, rhizome buds were dominant, in the LD, tiller buds were dominant, and in the MD, root-sprouting buds were dominant; (ii) total bud bank and cyperaceae bud density decreased with increasing degradation gradient, the density of leguminosae was insignificant in each degradation gradient, and the density of gramineae and forb were dominant in LD and MD meadows, respectively; (iii) total bud bank density was significantly and positively correlated with total above-ground biomass in the LD gradient, tiller bud density was significantly positively correlated with the species diversity index of above-ground vegetation under the ND gradient, rhizome bud density was significantly and positively correlated with total above-ground biomass in the LD gradient, and root-sprouting density was significantly negatively correlated with total above-ground biomass in ND meadows, but was significantly positively correlated with the species diversity index of the LD gradient. Therefore, our research shows that rhizome buds are more important in ND meadow habitats, tiller buds are more important in LD meadow habitats, and root-sprouting buds are more important in MD meadows. The response of bud banks to degradation gradient varies with different types of bud banks and different functional groups of plants, and the survival strategy of bud banks is of great value for community restoration and regeneration, which should be paid more attention to in subsequent alpine meadow research.